Comparison between commercial and synthesised nano flower-like rutile TiO2 immobilised on green super adsorbent towards dye wastewater treatment - Alias, Siti Salwa; Harun, Zawati; Azhar, Faiz Hafeez; Ibrahim, Siti Aida; Johar, Banjuraizah (Elsevier, 2020)
The combination of a semiconductor metal oxide with green low-cost adsorbent materials has prompted the emergence of new natural resources having higher efficiency for treating dye wastewater. This study investigated the characterisation and performance of synthesised nano flower-like rutile TiO2 (FeTiO2) via the facile hydrothermal method and sintered commercial TiO2 (CeTiO2). Both CeTiO2 and FeTiO2 were immobilised on green super adsorbent basil seed. The details of the structural properties were analysed by Rietveld refinement and the deconvolution method to verify the purity. The synthesised F eTiO2 immobilised on basil seed (BeFeTiO2) was found to have optimum physical and morphology properties. Kinetic and equilibrium studies illustrated that the adsorption behaviour of BeFeTiO2 could be better described by pseudo-second-order kinetic (chemisorption). The maximum uptake capacity (49.47 mg g 1) with the highest removal of methylene blue (98.95%) was obtained at an equilibrium time of 180 min following photocatalysis and self-cleaning. A large antibacterial ring area (1.83 mm2) was also obtained from BeFeTiO2. The removal of methylene blue dye for BeFeTiO2 increased as the recycle times increased (3 times) due to the increase of the surface area exposed to methylene blue as the weight of BeFeTiO2 immobilised on basil seed decreased. This demonstrates that BeFeTiO2 provides better potential to apply as a multifunction green super adsorbent for dye wastewater treatment compared to B eCeTiO2.